Perkaitan di antara Keadaan Tempat Kerja dengan Komitmen Guru - Yahadi, Yasili (1998)
This study was conducted on 217 teachers as respondents from ten secondary school in the district of Kota Kinabalu, Sabah. The aim of this study was to determine the relationship between factors relating to workplace conditions and defined demographic characteristics as against the teachers’ commitment towards work and responsibilities in school. Factors relating to place of work and teachers’ commitment cover workload, work autonomy, school style of management and the teachers’ social relationships. Whereas demographic characteristics cover sex, age, marital status, length of service and teachers’ category. This study will determine whether there is any specific or valid relationship on the said factors or vise versa. In this study, there are ten questions and ten hypothesis which have to be explained and answered. Meanwhile the methods of data analysis program were computed based on the analysis program found in the Statistical Package For The Social Sciences (SPSS). The methods of analysis used were t-Test, One-way ANOVA, Pearson Correlation and Multiple Regression. The t-Test analysis was used to determine whether there were valid differences in the teachers’ commitment based on the sex, category and marital status; One-way ANOVA was used to determine the differences based on the age and length of service; the Pearson Correlation was used to determine the relationship between the teachers’ commitment with the workload, work autonomy, style of management in school and the teachers’ social relationship as an individual; while the Multiple Regression was used to determine the relationship between the teachers’ commitment with the workload, work autonomy, management style and teachers’ social relationship as a group. The result of the study showed that the factors relating that covered workload, work autonomy, style of management in school, and the teachers’ social relationship had an effect on the teachers’ commitment. Analysis indicated that the four factors analysed could relate about 50% of the teachers’ commitment i.e. 37% through the school’s style of management, followed by 11% through workload, 2% through work autonomy and 1% through the teachers’ relationship. It showed that the schools’ style of management played a very important role and effect on the teachers’ commitment. Nevertheless, 50% of the factors associated with work place conditions could not be related. Thus, further survey has to be conducted to verify these other related factors. From the demographic characteristic point of view, it was found that the marital status had an effect on the teachers’ commitment. Analysis showed that the married teachers’ had a higher work commitment as compared to the single teachers’, whereas personal characteristics covering sex, age, length of service and category did not have any effect on the teachers’ commitment. It hoped that the result of this study could be used as reference for the school administration to improve achievement, administration effectiveness and school management. The quality of the school administration and management should always be reviewed, analysed and improved to realise and achieve the expectation of the Education Ministry to make the Malaysian System of Education a world standard. This effort is important so that the vision can be achieved as soon as possible.